METODE SPATIAL AUTOREGRESSIVE DALAM MEMODELKAN MASYARAKAT YANG BERPERILAKU MCK DI SUNGAI - DEWI P, KOMANG KOKOM SUCAHYATI; SUSILAWATI, MADE; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 6 No 4 (2017), 2017)
Spatial autoregressive (SAR) is a model of spatial regression which assumes that autoregressive process is only for the dependent variable by considering the spatial effect. The spatial effect consists of spatial dependence and spatial heterogeneity. One of problems which considers spatial effect is the case of society which do public bathing, washing, and toilets facilities (PBWTF) in the river, in Blahbatuh District. The aim of this research is to obtaine the model of society which still do PBWTF in the river, in Blahbatuh Districts in 2016 and to determine the factors that influence it. In this research, we obtained the model which is able to illustrate the case of society which do PBWTF and the factors that influence it such as the amount of householde which do not have latrine and the amount of family who lives near the river in every subvillage in Blahbatuh District .   Keywords : SAR, Spatial Effect, and Public Bathing, Washing, and Toilets Facilities in the River.